2017
DOI: 10.3389/fpsyg.2017.01321
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Age Cues in Resumes: Subtle Effects on Hiring Discrimination

Abstract: Anonymous resume screening, as assumed, does not dissuade age discriminatory effects. Building on job market signaling theory, this study investigated whether older applicants may benefit from concealing explicitly mentioned age signals on their resumes (date of birth) or whether more implicit/subtle age cues on resumes (older-sounding names/old-fashioned extracurricular activities) may lower older applicants’ hirability ratings. An experimental study among 610 HR professionals using a mixed factorial design s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 91 publications
(205 reference statements)
1
41
0
1
Order By: Relevance
“…Employment provides a number of non-economic latent functions (Jahoda, 1982 ), such as a daily structure and regular activity, a sense of self-efficacy, or identity and social status, which are lost when an individual is forced out of work. Human Resource Management practices designed for older workers (i.e., ER programs, among others) are perceived as a sign that they belong to a devalued social group (Hennekam and Herrbach, 2015 ; Kmicinska et al, 2016 ; Derous and Decoster, 2017 ). As a result, organizations should avoid forcing workers who show resistance to ER programs to retire, because the adverse effects on the individuals, their families, and health and social protection systems are disproportionate in comparison with the economic gain of this measure.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Employment provides a number of non-economic latent functions (Jahoda, 1982 ), such as a daily structure and regular activity, a sense of self-efficacy, or identity and social status, which are lost when an individual is forced out of work. Human Resource Management practices designed for older workers (i.e., ER programs, among others) are perceived as a sign that they belong to a devalued social group (Hennekam and Herrbach, 2015 ; Kmicinska et al, 2016 ; Derous and Decoster, 2017 ). As a result, organizations should avoid forcing workers who show resistance to ER programs to retire, because the adverse effects on the individuals, their families, and health and social protection systems are disproportionate in comparison with the economic gain of this measure.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Those studies typically demonstrate old age to be disadvantageous in comparison to young age (e.g., Fritzsche & Marcus, 2013; Krings et al., 2011). Recently, the investigation of implicit age cues (e.g., age‐associated characteristics or activities) in job applications received attention, too (Abrams et al., 2016; Derous & Decoster, 2017), mainly confirming the explicit age biases. Those studies are a first step toward a better understanding of the influence of implicit age cues on decision making in the hiring process.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the effect of omission on résumés and cover letters has not yet been tested, unlike other impression management tactics (Waung et al, ). A research recently tested the effect of partial omission (date of birth) in résumés and concluded that omitting explicit cues related to age lead to lower job suitability ratings because this might have to do with codes of conduct, what recruiters deem appropriate to be mentioned in resumes, (Derous & Decoster, ). In many Western European countries, it is good practice to indicate information like date of birth or photography on one's résumé, and not doing so might deviate from the social norm and result in overall lower ratings.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research has examined the impact of stereotypes on résumé screening and concluded that some cues lead to discriminatory behavior during the preselection process, including ethnic origin (Banerjee, Tolbert, & DiCiccio, ; Derous, Ryan, & Serlie, ), gender (Heilman, Martell, & Simon, ), obesity (Giel et al, ; Swami, Chan, Wong, Furnham, & Tovée, ), and age (Derous & Decoster, ). These converging results describe several persisting biases that anonymity may be able to reduce.…”
Section: Introductionmentioning
confidence: 99%